A Reporte of the Kingdom of Congo: Framing and Translating African Travel Writing for an Early Modern Readership - Brownlees, Nicholas (Status Quaestionis, 2019)
This article examines the translation into English of one of the most successful and important books about Africa of the early modern period. The source Italian text was entitled Relatione del reame di Congo et delle circonvicine contrade (Rome 1591) and within seven years this account of the Congo by Filippo Pigafetta had been translated into Dutch, English, German and Latin with further editions in the seventeenth century. The article argues that the paratextual framing of the English translation deserves analysis on three interrelated counts. First, for the manner in which the title-page brings to the fore probable unstated commercial interests behind the publication of the translation of this travel text; secondly, for what the English translator, Abraham Hartwell, writes in his address “to the Reader” regarding his own approach to translation and more generally his critique of contemporary translation practice; thirdly, for his use of marginalia in the body of the text.